160 IMPACT OF TREATMENT WITH INFLIXIMAB ON ANTICYCLIC CITRULLINATED PEPTIDE ANTIBODY AND RHEUMATOID FACTOR IN PATIENTS WITH RHEUMATOID ARTHRITIS. (1st January 2006) - Mubashir, E.; Ahmed, M. M.; Wolf, R. E.; Hayat, S.; Hall, V. C.; Shi, R.; Berney, S. M.
Abstract : Background: Several studies have detected that the level of IgM-RF decreases with effective disease modifying antirheumatic drugs (DMARDs), especially methotrexate and parental gold. In contrast, few studies have analyzed the variations in the titer of anticyclic citrullinated peptide (anti-CCP) antibody or rheumatoid factor (RF) during treatment with TNFa inhibitors. Purpose: To investigate the impact of infliximab treatment on anti-CCP antibody and RF levels in patients with rheumatoid arthritis (RA). Methods: Sera from 33 RA patients receiving infliximab plus other DMARDs were tested for anti-CCP antibody, IgA-, IgG-, and IgM-RF using a commercially available semi-quantitative ELISA at baseline and 30 and 54 weeks after treatment. Results: Patients had a mean age 6 SD of 54.6 6 12.1 years and a mean disease duration 6 SD of 12.9 6 8.3 years and were predominantly female (n = 28; 85%). At baseline, 27 of the 33 patients (81.8%) were positive for anti-CCP antibody, 28 (84.8%) for IgA-RF, 27 (81.8%) for IgG-RF, and 29 (87.8%) for IgM-RF. The proportion of patients who were positive for anti-CCP antibody (81.8% vs 78.5%), IgA-RF (84.8% vs 85.7%), IgG-RF (81.8% vs 85.7%), and IgM-RF (87.8% vs 89.2%) was similar at baseline and at 54 weeks. Serum levels of anti-CCP antibody and IgA-RF decreased significantly after 30 weeks; however, the decrease was not significant at week 54. The decrease in IgG-RF titers was not significant at 30 and 54 weeks. IgM-RF titers decreased significantly at 30 and 54 weeks. A strong correlation between anti-CCP and IgA-, IgG-, and IgM-RF was observed at baseline (Spearman's correlation coefficients (r) = .48, .43, .65, p = < .05) and after infliximab treatment at 30 weeks (r = .45, .46, .62, p = < .05) and 54 weeks (r = .49, .45, .60, p = < .05). Conclusion: Treatment with infliximab results in decreased anti-CCP antibody and IgA-RF early in the course of therapy that is not sustained. IgM-RF declines and remains decreased for at least 54 weeks. Investigations in larger cohorts of RA patients (especially early RA) with longer follow-up are needed to assess the impact of specific therapeutic interventions on anti-CCP antibody and RF levels and their relationship to disease activity.